Institutions Developing Excellence in Academic Leadership (IDEAL): A partnership to advance gender equity, diversity, and inclusion in academic STEM. Issue 3 (15th April 2019) - Bilimoria, Diana; Singer, Lynn T.
Abstract : Purpose: The purpose of this paper is to describe the objectives, activities and outcomes of the National Science Foundation ADVANCE project, Institutions Developing Excellence in Academic Leadership (IDEAL) during 2009–2012. The goal of IDEAL was to create an institutional learning community empowered to develop and leverage knowledge, skills, resources and networks to transform academic cultures and enhance gender equity, diversity and inclusion in science, technology, engineering and math (STEM) disciplines at six research universities in the northern Ohio region. Over the three-year period, these institutions developed academic leaders and institutionalized gender equity transformation through multi-dimensional and multi-level initiatives, improving the advancement and leadership of women faculty in STEM disciplines. Design/methodology/approach: The authors describe the objectives, activities and outcomes of the NSF ADVANCE project, IDEAL during 2009–2012. The six research institutions included in IDEAL were Bowling Green State University, Case Western Reserve University (the lead institution), Cleveland State University, Kent State University, University of Akron and University of Toledo. Findings: IDEAL's outcomes included the institutionalization of a number of gender equity initiatives at each university, an increase in the number of tenured women faculty in science and engineering disciplines over three years across the six universities, and increases in the numbers of women in faculty and administrative leadership positions. Out of 62 of the IDEAL participants (co-directors and change leaders), 25 were promoted or appointed to roles of leadership within or beyond their institutions during or after their participation in IDEAL. A number of new institutional collaborations and exchanges involving the six universities occurred during and emerged from IDEAL. An integrative model of the IDEAL program is developed, describing the nested components of each institution's gender equity transformation within the IDEAL partnership consortium and the larger NSF ADVANCE community, and highlighting the dynamic interactions between these levels. Social implications: The IDEAL program demonstrates that systemic change to achieve equity for women and underrepresented minority faculty in STEM disciplines must be rooted on individual campuses but must also propagate among higher education systems and the broader scientific community. The effort to develop, sustain and expand the IDEAL partnership model of institutional transformation (IT) in higher education illuminates how innovative, context-sensitive, cost-effective and customized institutional strategies may be implemented to advance gender equity, diversity, inclusion and leadership of women faculty at all levels across the country. Originality/value: This is an original description of a unique and distinctive partnership among research universities to foster gender equity IT. The manuscript details the objectives, activities and outcomes of the IDEAL program, established with the aim of broadening participation in the STEM academic workforce and advancing gender equity, diversity and inclusion in institutions of higher education. An integrative model is developed, illustrating the key components and outcomes of the IDEAL program.